Hadith #2256 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
Ibn ‘Abbas said “Hilal bin Umayyah was one of the three persons whose repentance was accepted by Allaah. One night he returned from his land and found a man along with his wife. He witnessed with his eyes and heard with his ears. He did not threaten him till the morning.” Next day he went to the Apostle of Allaah(ﷺ) in the morning and said Apostle of Allaah(ﷺ) “I came to my wife in the night and found a man along with her. I saw with my own eyes and heard with my own ears. The Apostl
Grade: Da'if

Hadith #2257 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
Ibn ‘Umar said “The Apostle of Allaah(ﷺ) said to the spouses who invoked curses on each other. Your reckoning is in Allaah’s hands for one of you is liar there is no way for you to (remarry) her. He then asked Apostle of Allaah(ﷺ) what about my property? He replied “There is no property for you. If you have spoken the truth, it is the price for your having had the right to intercourse with her and if you have lied against her it is still more remote for you.
Grade: Sahih

Hadith #2296 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Maimun bin Mihram said “I came to Median and went to Sa’id bin Al Musayyab”. I said (to him) Fathimah daughter of Qais was divorced and she shifted from her house. Sa’id said “This woman has perverted people. She was arrogant so she was placed with Ibn Umm Makhtum, the blind.”
Grade: Da'if

Hadith #2324 - Sunan Abi Dawud - Abdullah bin Abi Labid عبد الله بن أبي لبيد; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; Aisha bint Abi Bakr; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير (Sunan Abi Dawud)
The Prophet (ﷺ) said: The end of Ramadan is on the day when you end it, and the ‘Id (festival) of sacrifice is on the day when you sacrifice. The whole of Arafah is the place of staying, and the whole of Mina is the place of sacrifice, and all the roads of Mecca are the place of sacrifice, and the whole of Muzdalifah is the place of staying.
Grade: Sahih

Hadith #2335 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Tauba al-'Anbari al-Basri توبة العنبري البصري; Umm Salamah (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Do not fast one day or two days just before Ramadan, except in the case of a man who has been in the habit of observing the particular fast, for he may fast on that day.
Grade: Sahih

Hadith #2350 - Sunan Abi Dawud - Abdullah bin Da'ud al-Kharaybi عبد الله بن داود أبو عبد الرحمن الخريبي; Ahmad bin Hanbal أحمد بن حنبل; Hisham bin 'Urwa هشام بن عروة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Urwa ibn al-Zubayr عروة بن الزبير; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: When any of you hears the summons to prayer while he has a vessel in his hand, he should not lay it down till he fulfils his need.
Grade: Hasan Sahih

Hadith #2355 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Anas ibn Malik; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of you is fasting, he should break his fast with dates; but if he cannot get any, then (he should break his fast) with water, for water is purifying.
Grade: Hasan Sahih

Hadith #2366 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmad bin Hanbal أحمد بن حنبل; Amr bin Marthad, Abu Asma' al-Rahbi عمرو بن مرثد أبو أسماء الرحبي; Hisham bin 'Urwa هشام بن عروة; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Thawban bin Bujdud; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: Snuff up water freely unless you are fasting.
Grade: Sahih

Hadith #2367 - Sunan Abi Dawud - Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmad bin Hanbal أحمد بن حنبل; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man who cupped and a man who has himself cupped broke their fast. The narrator Shayban said in his version: AbuQilabah told me that AbuAsma’ ar-Rahbi told him that Thawban, the client of the Messenger of Allah (ﷺ), told him that he heard the Prophet (ﷺ) say this.
Grade: Sahih

Hadith #2369 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Makhul al-Shami/al-Damashiqi مكحول الشامي; Muhammad bin Bakr bin 'Uthman al-Barsani محمد بن بكر بن عثمان البرساني; Uthman bin Muhammad (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came to a man at al-Baqi’ while he was cupping on the 18th of Ramadan ; he (the Prophet) was holding my hand. Thereupon he said: A man who cups and a man who gets himself cupped break their fast. Abu Dawud said: The narrator Khalid al-Hadhdha’ transmitted a similar tradition from Abu Qilabah through a different chain of narrators mentioned by the narrator Ayyub.
Grade: Sahih

Hadith #2373 - Sunan Abi Dawud - Abdur Rahman bin 'Abis al-Nakha'i عبد الرحمن بن عابس النخعي; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) had himself cupped when he was fasting and wearing ihram (pilgrim garb).
Grade: Da'if

Hadith #2396 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Ammara bin al-Q'aqa' bin Shabrma عمارة بن القعقاع بن شبرمة; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone breaks his fast one day in Ramadan without a concession granted to him by Allah, a perpetual fast will not atone for it.
Grade: Da'if

Hadith #2430 - Sunan Abi Dawud - Abdullah bin Abi Labid عبد الله بن أبي لبيد; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير (Sunan Abi Dawud)
I asked Sa’id b. Jubair about fasting during Rajab. He said: Ibn ‘Abbas told me that the Messenger of Allah (ﷺ) used to fast to such an extent that we thought that he would never break his fast; and he would go without fasting to such an extent that we thought he would never fast.
Grade: Sahih

Hadith #2447 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Amr bin Aws bin Abi Aws عمرو بن أوس بن أبي أوس; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sufyan bin 'Uyaynah سفيان بن عيينة; Umar ibn al-Khattab (Sunan Abi Dawud)
AbdurRahman reported on the authority of his uncle that the people of the tribe Aslam came to the Prophet (ﷺ). He said (to them): Did you fast on this day? They replied: No. He said: Complete the rest of your day, and make atonement for it.
Grade: Da'if

Hadith #2576 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Uqba bin Khalid bin 'Uqba - al-Majdar عقبة بن خالد بن عقبة السكوني المجدر (Sunan Abi Dawud)
The Prophet (ﷺ) used to make lean by training horses which he employed in the race.
Grade: Sahih

Hadith #2689 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Abbas; Ikrama bin 'Ammar عكرمة بن عمار العجلي أبو عمار اليمامي; Umar ibn al-Khattab (Sunan Abi Dawud)
Jubair bin Mut’im reported the Prophet (ﷺ) as saying about the prisoners taken at Badr. If Mut’im bin ‘Adi had been alive and spoken to me about these filthy ones, I would have left them for him.
Grade: Sahih

Hadith #2718 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Auf bin Malik al-Ashja'i; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي (Sunan Abi Dawud)
Anas reported the Apostle of Allaah(ﷺ) as saying “He who kills and infidel gets his spoil.” Abu Talhah killed twenty men that day meaning the day of Hunain and got their spoils. Abu Talhah met Umm Sulaim who had a dagger with her. He asked “What is with you, Umm Sulaim”? She replied “I swear by Allaah, I intended that if anyone came near me I would pierce his belly with it. Abu Talhah informed the Apostle of Allaah(ﷺ)about it. Abu Dawud said “This is good (hasan) tradition.” Ab
Grade: Sahih

Hadith #2719 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Auf bin Malik al-Ashja'i; Jubayr bin Nufayr al-Hadrami; Khalid bin Ma'dan خالد بن معدان; Nufayr bin Malik al-Hadrami; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
‘Awf bin malik Al Ashja’I said “I went out with Zaid bin Harith in the battle of Mutah. For the reinforcement of the Muslim army a man from the people of Yemen accompanied me. He had only his sword with him. A man from the Muslims slaughtered a Camel. The man for the reinforcement asked him for a part of its skin which he gave him. He made it like the shape of a shield. We went on and met the Byzantine armies. There was a man among them on a reddish horse with a golden saddle and golden we
Grade: Sahih

Hadith #2729 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Zayd bin 'Abdullah محمد بن زيد بن عبد الله بن عمر; Umayr Mawla Abi Laham al-Ghafari (Sunan Abi Dawud)
Hashraj ibn Ziyad reported on the authority of his grandmother that she went out with the Messenger of Allah (ﷺ) for the battle of Khaybar. They were six in number including herself. (She said): When the Messenger of Allah (ﷺ) was informed about it, he sent for us. We came to him, and found him angry. He said: With whom did you come out, and by whose permission did you come out? We said: Messenger of Allah, we have come out to spin the hair, by which we provide aid in the cause of Allah. We
Grade: Da'if

Hadith #2732 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
A’ishah said (this is the version of narrator Yahya). A man from the polytheists accompanied the Prophet (ﷺ) to fight along with him. He said “Go back. Both the narrators (Musaddad and Yahya) then agreed. The Prophet said “We do not want any help from a polytheist.”
Grade: Sahih

Hadith #2733 - Sunan Abi Dawud - Abdullah bin Yazid bin Zayd; Abdur Rahman bin 'Abdullah bin 'Utba عبد الرحمن بن عبد الله بن عتبة المسعودي; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Sunan Abi Dawud)
Ibn ‘Umar said “The Apostle of Allaah(ﷺ) allotted three portions for a man and his horse, one for him and two for his horse.
Grade: Sahih

Hadith #2777 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Amir al-Sha'bi عامر الشعبي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Jabir ibn 'Abdullah; Siyar Abu al-Hakam al-Anzi سيار أبو الحكم العنزي (Sunan Abi Dawud)
The Prophet (ﷺ) said: The best time for a man to go in to his family on return from a journey is at the beginning of the night.
Grade: Sahih

Hadith #2806 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Ahmad bin Hanbal أحمد بن حنبل; Ata' bin Abi Rabah عطاء بن أبي رباح; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Jabir ibn 'Abdullah (Sunan Abi Dawud)
I asked Sa’id b. al-Musayyab: What is meant by animal with a slit ear and broken horn ? He replied: Half and more than half.
Grade: Sahih

Hadith #2849 - Sunan Abi Dawud - Adi ibn Hatim al-Tayyi'; Ahmad bin Hanbal أحمد بن حنبل; Amir al-Sha'bi عامر الشعبي; Asim al-Ahwal عاصم الأحول; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: When you shoot your arrow and mention Allah’s name, and you find it (the game) after a day, and you do not find it in water, and you find in it only the mark of you arrow, eat (it). But if another dog joins your dogs, do not eat it, for you do not know maybe the one which was not yours has killed it.
Grade: Sahih

Hadith #2885 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Knowledge has three categories; anything else is extra; a precise verse, or an established sunnah (practice), or a firm obligatory duty.
Grade: Da'if

Hadith #2922 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Da'ud bin al-Husain al-Amwy داود بن الحصين الأموي; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan Abi Dawud)
“To those also, to whom your right hand was pledged, give your portion.” When the Emigrants came to Medina. they inherited from the Helpers without any blood-relationship with them for the brotherhood which the Messenger of Allah (ﷺ) established between them. When the following verse was revealed: “To (benefit) everyone we have appointed shares and heirs to property left by parent and relatives.” it abrogated the verse: “To those also, to whom your right hand was pledged, give their
Grade: Sahih

Hadith #2955 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone leaves property, it goes to his heirs. And if anyone leaves dependents (without resources), they come to us.
Grade: Sahih

Hadith #2956 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: I am nearer to every believer than himself, and if anyone leaves, it goes to his heirs.
Grade: Sahih

Hadith #3006 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ibn Ishaq محمد بن إسحاق بن يسار‎; ibn Umar; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Nafie' نافع مولى ابن عمر; Umar ibn al-Khattab; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan Abi Dawud)
The Prophet fought with the people of Khaybar, and captured their palm-trees and land, and forced them to remain confined to their fortresses. So they concluded a treaty of peace providing that gold, silver and weapons would go to the Messenger of Allah (ﷺ), and whatever they took away on their camels would belong to them, on condition that they would not hide and carry away anything. If they did (so), there would be no protection for them and no treaty (with Muslims). They carried away a purs
Grade: Da'if

Hadith #3019 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; Aslam Client Of 'Umar أسلم مولى عمر; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Umar ibn al-Khattab; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) took out his fifth from the booty of Khaybar, and divided the rest of it among those who attended the battle and among those who were away from it but attend the expedition of al-Hudaybiyyah.
Grade: Hasan

Hadith #3030 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin 'Uyaynah سفيان بن عيينة; Umar ibn al-Khattab (Sunan Abi Dawud)
Jabir bin ‘Abd Allah said that he was told by ‘Umar bin Al Khattab that he heard the Apostle of Allaah(ﷺ) say “I will certainly expel the Jews and the Christians from Arabia and I shall leave only Muslims in it.”
Grade: Sahih

Hadith #3035 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
Abu Hurairah reported the Messenger of Allah (ﷺ) as saying “Iraq will prevent its measure (qafiz) and dirham. Syria will prevent its measure (mudi) and dinar. Egypt will prevent its measure (irdabb) and dinar. Then you will return to the position where you started. Zuhair said this three times. The flesh and blood of Abu Hurairah witnessed it.
Grade: Sahih

Hadith #3071 - Sunan Abi Dawud - Abdullah bin 'Umar bin Hafs bin 'Asim عبد الله بن عمر بن حفص بن عاصم; Ahmad bin Hanbal أحمد بن حنبل; Hmad bin Khalid al-Khyat حماد بن خالد الخياط القرشي; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
I came to the Prophet (ﷺ), and took the oath of allegiance to him. He said: If anyone reaches a water which has not been approached before by any Muslim, it belongs to him. The people, therefore, went out running and marking (on the land).
Grade: Da'if

Hadith #3076 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Hasan al-Basri الحسن البصري; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Qatada قتادة; Sa'id bin Abi Sa'id; Samra bin Jundub (Sunan Abi Dawud)
I testify that the Messenger of Allah (ﷺ) decided that the land is the land of Allah, and the servants are the servants of Allah. If anyone brings barren land into cultivation, he has more right to it. This tradition has been transmitted to us from the Prophet (ﷺ) by those who transmitted the traditions about prayer from him.
Grade: Da'if

Hadith #3095 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A young Jew became ill. The Prophet (ﷺ) went to visit him. He sat down by his head and said to him: Accept Islam. He looked at his father who was beside him near his head, and he said: Obey Abu al-Qasim. So he accepted Islam, and the Prophet (ﷺ) stood up saying: Praise be to Allah Who has saved him through me from Hell.
Grade: Sahih

Hadith #3119 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: When one of you is afflicted with a calamity, he should say: “We belong to Allah, and to Him we do return.” O Allah, I expect reward from Thee from this affliction, so give me reward for it, and give me a better compensation.
Grade: Sahih

Hadith #3147 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
Muhammad b. Sirin used to learn how to wash the dead from Umm ‘Atiyyah: he would was with lotus leaves twice and with water and camphor for the third time.
Grade: Sahih

Hadith #3148 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Ahmad bin Hanbal أحمد بن حنبل; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم (Sunan Abi Dawud)
The Prophet (ﷺ) made a speech one day and mentioned a man from among his Companions who died and was shrouded in a shroud of bad quality, and was buried at night. The Prophet (ﷺ) rebuked that man be buried at night until prayer was offered over him, except that a man was forced to do that. The Prophet (ﷺ) said: When one of you shrouds his brother, he should use a shroud of good quality.
Grade: Sahih

Hadith #3150 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Urwa ibn al-Zubayr عروة بن الزبير; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of you dies, and he possesses something, he should be shrouded in the garment of the Yemeni stuff.
Grade: Sahih

Hadith #3152 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Ahmad bin Hanbal أحمد بن حنبل; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Uthman bin Muhammad; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
“of cotton”. The narrator said: Aisha was told that the people said that he was shrouded in two garments and one cloak. She replied: A cloak was brought but they returned it and did not shroud him in it.
Grade: Sahih

Hadith #3156 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ibn Ishaq محمد بن إسحاق بن يسار‎; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan Abi Dawud)
The Prophet (ﷺ) said: The best shroud is a lower garment and one which covers the whole body, and the best sacrifice is a horned ram.
Grade: Hasan

Hadith #3224 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) prayed over the martyrs of Uhud after eight years like a man who bids farewell to the living and dead.
Grade: Sahih

Hadith #3249 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Umar ibn al-Khattab (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) found ‘Umar al-Khattab in a caravan while he was swearing by his father. So he said: Allah forbids you to swear by forefathers. If anyone swears, he must swear by Allah or keep silence.
Grade: Sahih

Hadith #3257 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Ahmad bin Hanbal أحمد بن حنبل; al-Husain bin Waqid ak-Mervzi الحسين بن واقد المروزي; Burayda bin al-Husayb; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
That he took oath of allegiance to the Messenger of Allah (ﷺ) under the tree. The Messenger of Allah (ﷺ) said: If anyone swears by religion other than Islam falsely, he is like what has has said. If anyone kills himself with something, he will be punished with it on the Day of Resurrection. A vow over which a man has no control is not binding on him.
Grade: Sahih

Hadith #3260 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Nafie' نافع مولى ابن عمر; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
A similar tradition has also been transmitted by Yusuf b. ‘Abd Allah b. Salam through a different chain of narrators.
Grade: Da'if

Hadith #3263 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ahmad bin Hanbal أحمد بن حنبل; Ikrama bin 'Ammar عكرمة بن عمار العجلي أبو عمار اليمامي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The oath which the Messenger of Allah (ﷺ) often used was this: No, by Him who overturns the hearts.
Grade: Sahih

Hadith #3266 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sufyan bin 'Uyaynah سفيان بن عيينة; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
We came to the Messenger of Allah (ﷺ) in a delegation. The Prophet (ﷺ) then said: By the age of thy god.
Grade: Hasan

Hadith #3324 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A similar tradition has also been transmitted by ‘Uqbah b. ‘Amir from the Prophet (ﷺ) through a different chain of narrators.
Grade: Sahih

Hadith #3338 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
I heard my father say: A man said to Shu’bah: Sufyan opposed you (i.e. narrated a tradition which differs from your version). He replied: You racked my mind. I have been told that Yahya b. Ma’in said: If anyone opposes Sufyan, the version of Sufyan will be acceptable.
Grade: Sahih

Hadith #3346 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Maharab bin Dithar محارب بن دثار; Mas'ar bin Kadam مسعر بن كدام; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) borrowed a young camel, and when the camels of the sadaqah (alms) came to him, he ordered me to pay the man his young camel. I said: I find only an excellent camel in its seventh year. So the Prophet (ﷺ) said: Give it to him, for the best person is he who discharges his debt in the best manner.
Grade: Sahih

Hadith #3373 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman bin Atyq سليمان بن عتيق; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) forbade the sale of fruits till they were clearly in good condition , and (ordered that) they should not be sold but for dinar or dirham except Araya.
Grade: Sahih

Hadith #3380 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade the transaction called habal al-habalah.
Grade: Sahih

Hadith #3403 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Jabir ibn 'Abdullah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sa'id bin Myna سعيد بن مينا (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone sows in other people’s land without their permission, he has no right to any of the crop, but he may have what it cost him.
Grade: Sahih

Hadith #3407 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade mukhabarah. I asked: What is mukhabarah ? He replied: That you have the land (for cultivation) for half, a third, or a quarter (of the produce).
Grade: Sahih

Hadith #3414 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Bakr bin 'Uthman al-Barsani محمد بن بكر بن عثمان البرساني; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
When Allah bestowed Khaybar on His Prophet (ﷺ) as fay’ (as a result of conquest without fighting), the Messenger of Allah (ﷺ) allowed (them) to remain there as they were before, and apportioned it between him and them. He then sent Abdullah ibn Rawahah who assessed (the amount of dates) upon them.
Grade: Sahih

Hadith #3432 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
I heard the Prophet (ﷺ) say … narrating the tradition to the same effect.
Grade: Da'if

Hadith #3448 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Alqama bin 'Abdullah علقمة بن عبد الله بن سنان; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل (Sunan Abi Dawud)
Hoarding does not apply to dried dates. Ibn al-Muthanna said that he (Yahya b. Fayyad) reported on the authority of al-Hasan. We (Ibn al-Muthanna) said to him (Yahya): Do not say: “on the authority of al-Hasan.” Abu Dawud said: This tradition according to us is false. Abu Dawud said: Sa’id b. al-Musayyab used to hoard kernel, fodder, and seeds. Abu Dawud said: I heard Ahmad b. Yunus say: I asked Sufyan about hoarding fodder. He replied: They (the people in the past) disapproved of hoarding
Grade: Da'if

Hadith #3451 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The people said: Messenger of Allah , prices have shot up, so fix prices for us. Thereupon the Messenger of Allah (ﷺ) said: Allah is the one Who fixes prices, Who withholds, gives lavishly and provides, and I hope that when I meet Allah, none of you will have any claim on me for an injustice regarding blood or property.
Grade: Sahih

Hadith #3479 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) forbade payment for dog and cat.
Grade: Sahih

Hadith #3493 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
During the time of Messenger of Allah (ﷺ) we used to buy grain, and he sent a man to us who ordered us to move it from the spot where we had bought it to some other place, before we sold it without weighing or measuring it.
Grade: Sahih

Hadith #3512 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
Ibn Mas’ud sold slaves to al-Ash’ath b. Qais. He then narrated the rest of the tradition to the same effect with some variation of words.
Grade: Sahih

Hadith #3513 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: There is the right of option regarding everything which is shared, whether a dwelling or a garden. It is not lawful to sell before informing one’s partner, but if he sells without informing him, he has the greatest right to it.
Grade: Sahih

Hadith #3517 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Ahmad bin Hanbal أحمد بن حنبل; Ata' bin Abi Rabah عطاء بن أبي رباح; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Jabir ibn 'Abdullah (Sunan Abi Dawud)
The Prophet (ﷺ) said: A neighbour has the best claim to the house or land of the neighbour.
Grade: Sahih

Hadith #3554 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
A similar tradition has been transmitted by ‘Aqil from Ibn Shihab and by Yazid b. Abi Habib from Shihab. Al-Auza’i’s wordings vary from those of Ibn Shihab. Fulaih b. Sulaiman also narrated the tradition like that of Malik.
Grade: Sahih

Hadith #3557 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) decided a case of a woman from the Ansar to whom an orchard of date-palms was given by her son. She then died. Her son said: I gave it to her for her life, and she has brothers. Thereupon the Messenger of Allah (ﷺ) said: It belongs to her during her life and after death. He then said: I gave a sadaqah (charity to her. He replied: It is more unexpected from you.
Grade: Da'if

Hadith #3578 - Sunan Abi Dawud - Abu Burda bin Niyar; Ahmad bin Hanbal أحمد بن حنبل; Hameed bin Hilal حميد بن هلال; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qurrah bin Khalid al-Sadusi قرة بن خالد السدوسي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone desires the office of Judge and seeks help for it, he will be left to his own devices; if anyone does not desire it, nor does he seek help for it, Allah will send down an angel who will direct him aright. Waki’ said: (This tradition has also been transmitted) by Isra’il, from ‘Abd al-A’la, from Bilal bin Abi Musa, from Anas, from the Prophet (ﷺ). Abu ‘Awanah said: from ‘Abd al-A’la, from Bilal bin Mirdas al-Fazari, from Khaithamah al-Basri from A
Grade: Da'if

Hadith #3616 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد; Salmah bin Shbyb سلمة بن شبيب (Sunan Abi Dawud)
Two men disputed about some property and brought the case to the Holy Prophet (ﷺ), but neither of them could produce any proof. So the Holy Prophet (ﷺ) said: Cast lots about the oath whatever it may be, whether they like it or dislike it.
Grade: Sahih

Hadith #3668 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Amir al-Sha'bi عامر الشعبي; ibn Umar; Umar ibn al-Khattab; Yahya bin Sa'id bin Hiyan يحيى بن سعيد بن حيان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to me: recite Surat al-Nisa’. I asked: Shall I recite to you what was sent down to you? He replied: I like to here it from someone else. So I recited (it) until I reached this verse “How then shall it be when We bring from every people a witness?”. Then I raised my head and saw tears falling from his eyes.
Grade: Sahih

Hadith #3687 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Hatm bin Hryth al-Ta'iy حاتم بن حريث الطائي المحري; Malik bin Abi Maryam مالك بن أبي مريم الحكمي; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: Every intoxicant is forbidden; if a faraq of anything causes intoxication, a handful of it is forbidden.
Grade: Sahih

Hadith #3713 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Aisha bint Abi Bakr; Ata' bin Abi Rabah عطاء بن أبي رباح; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Ibn Jurayj ابن جريج; Ubaid bin 'Umayr bin Qatada عبيد بن عمير بن قتادة (Sunan Abi Dawud)
Raisins were steeped for the Prophet (ﷺ) and he would drink it in the morning and the night after, the following day and the night after. He then gave orders and it was given to servants to drinks or poured away. Abu Dawud said: That “it was given to servants to drink” means before it spoiled. Abu Dawud said: Abu ‘Umar Yahya al-Bahrani.
Grade: Sahih

Hadith #3730 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I was in the house of Maymunah. The Messenger of Allah (ﷺ) accompanied by Khalid ibn al-Walid entered. Two roasted long-tailed lizards (dabb) placed on the sticks were brought to him. The Messenger of Allah (ﷺ) spat. Khalid said: I think that you abominate it, Messenger of Allah. He said: Yes. Then the Messenger of Allah (ﷺ) was brought milk, and he drank (it). The Messenger of Allah (ﷺ) then said: When one of you eats food, he should say: O Allah, bless us in it, and give us food (or no
Grade: Hasan

Hadith #3756 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A companion of the Prophet (ﷺ) reported him as saying: When two people come together to issue an invitation, accept that of the one whose door is nearer in neighbourhood, but if one of them comes before the other accept the invitation of the one who comes first.
Grade: Da'if

Hadith #3775 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The tradition mentioned above has been transmitted by al-Zuhri from a different chain of narrators.
Grade: Sahih

Hadith #3806 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
I went with the Messenger of Allah (ﷺ) to fight at the battle of Khaybar, and the Jews came and complained that the people had hastened to take their protected property (as a booty), so the Messenger of Allah (ﷺ) said: The property of those who have been given a mules, every fanged beast of prey, and every bird with a talon are forbidden for you.
Grade: Da'if

Hadith #3824 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Zirr ibn Hubaysh said: Hudhayfah traced, I think, to the Messenger of Allah (ﷺ) the saying: He who spits in the direction of the qiblah will come on the Day of Resurrection in the state that his saliva will be between his eyes; and he who eats from this noxious vegetable should not come near our mosque, saying it three times.
Grade: Sahih

Hadith #3843 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The tradition mentioned above (No. 3833) has also been transmitted by Ibn Abbas from Maymunah, from the Prophet (ﷺ) like the tradition narrated by az-Zuhri, from Ibn al-Musayyab.
Grade: Da'if

Hadith #3867 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) snuffed medicine.
Grade: Sahih

Hadith #3871 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
When a physician consulted the Prophet (ﷺ) about putting frogs in medicine, he forbade him to kill them.
Grade: Sahih

Hadith #3878 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Wear your white garments, for they are among your best garments, and shroud your dead in them. Among the best types of collyrium you use is antimony (ithmid): it clears the vision and makes the hair sprout.
Grade: Sahih

Hadith #3884 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmad bin Hanbal أحمد بن حنبل; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin Yahya bin 'Ammara عمرو بن يحيى بن عمارة; Da'ud bin 'Abdur Rahman al-'Atar داود بن عبد الرحمن العطار; Yahya bin 'Ammara يحيى بن عمارة بن أبي حسن الأنصاري (Sunan Abi Dawud)
The Prophet (ﷺ) said: No spell is to be used except for the evil eye or a scorpion sting.
Grade: Sahih

Hadith #3918 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa bin 'Amir; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
People said: safar is a pain within the belly. I asked: What is hamah ? He said: People said (believed) that hamah which is an owl or a nightbird and which shrieks is the spirit of men. It is not the spirit of men. It is an animal.
Grade: Sahih

Hadith #3946 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
If a man emancipates his share in a slave, the rest will be emancipated by his money if he has enough money to pay the full price for him.
Grade: Sahih

Hadith #3947 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
If a man is shared by two men, and one of them emancipates his share, a price of the slave will be fixed, not more or less, and he will be emancipated by him in case he is rich.
Grade: Sahih

Hadith #3954 - Sunan Abi Dawud - Abdul Malik bin Aby عبد الملك بن أبي سليمان; Ahmad bin Hanbal أحمد بن حنبل; Ata' bin Abi Rabah عطاء بن أبي رباح; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Jabir ibn 'Abdullah; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين (Sunan Abi Dawud)
We sold slave-mothers during the time of the Messenger of Allah (ﷺ) and of AbuBakr. When Umar was in power, he forbade us and we stopped.
Grade: Sahih

Hadith #3956 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) said: You are more entitled to his price, and Allah has no need of it.
Grade: Sahih

Hadith #3991 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata' bin Abi Rabah عطاء بن أبي رباح; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) read: “(There is for him) Rest and satisfaction” (faruhun wa rayhan).
Grade: Hasan

Hadith #3999 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) mentioned the name of the one who will sound the trumpet (sahib as-sur) and said: On his right will be Jibra’il and on his left will be Mika’il.
Grade: Da'if

Hadith #4142 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Jabir bin Samra; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) mentioned bedding and said: There should be bedding for a man, bedding for his wife, and third for a guest, but a fourth for the devil.
Grade: Sahih

Hadith #4167 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
That he heard Mu’awiyah b. Abi Sufyan say during the Hajj when he was on the pulpit and took a lock of hair which was in the hand of the guard, saying: O people of Medina, where are your scholars ? I heard the Messenger of Allah (ﷺ) forbidding such a think as this and said: The children of Isra’il perished when their women practised it.
Grade: Sahih

Hadith #4170 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sa'id bin Jubayr سعيد بن جبير الأسدي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر (Sunan Abi Dawud)
The woman who supplies fake hair and the one who asks for it, the woman who pulls out hair for other people and the woman who depilates herself, the woman who tattoos and the one who has it done when there is no disease to justify it have been cursed. Abu Dawud said: Wasilah means the woman who adds false hair to the hair of women. Mustawsilah means the one who asks for adding the hair to her hair. namisah means a woman who plucks hair from the brow until she makes it thin; mutanammisah means th
Grade: Sahih

Hadith #4192 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Umar bin Naf' al-Dwy عمر بن نافع العدوي (Sunan Abi Dawud)
The Prophet (ﷺ) gave the children of Ja’far three day’ time to visit them. He then came to visit them, and said: Do not weep over my brother after this day. He said: Call to me the children of my brother. We were brought to him as if we were chicken. He said: Call a barber to me. He then ordered and our heads were shaved.
Grade: Sahih

Hadith #4194 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
the Prophet (ﷺ) forbade qaza’ which means that the head of a boy is shaved and a lock is left.
Grade: Sahih

Hadith #4274 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; al-Mughira bin al-Nu'man al-Nakha'i المغيرة بن النعمان النخعي الكوفي; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The verse: “Those who invoke not with Allah” applied to polytheists. He said: About them another verse, “Say: O my servants who have transgressed against their souls” was also revealed.
Grade: Sahih

Hadith #4346 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan Abi Dawud)
He who sees it and disapproves of it will be like him who was not present.
Grade: Hasan

Hadith #4349 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ayoub al-Sakhtiyani أيوب السختياني; Ikrama عكرمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah will not fail to detain this community for less than half a day.
Grade: Sahih

Hadith #4352 - Sunan Abi Dawud - Abu Burda bin Niyar; Ahmad bin Hanbal أحمد بن حنبل; Hameed bin Hilal حميد بن هلال; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qurrah bin Khalid al-Sadusi قرة بن خالد السدوسي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The blood of a Muslim man who testifies that there is no god but Allah and that I am the Messenger of Allah should not be lawfully shed but only for one of three reasons: married fornicator, soul for soul, and one who deserts his religion separating himself from the community.
Grade: Sahih

Hadith #4381 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sufyan bin 'Uyaynah سفيان بن عيينة; Umarh bint 'Abdur Rahman عمرة بنت عبد الرحمن بن سعد بن زرارة (Sunan Abi Dawud)
A man came to the prophet (ﷺ) and said : Messenger of Allah ! I have committed a crime which involves prescribed punishment so inflict it on me . He said : Have you not performed ablution when you came? He said : Yes, He said: Have you not prayed with us when we prayed ? He said : Yes .He then said : Go off, for Allah, the Exalted, forgave you.
Grade: Sahih

Hadith #4384 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; Ibn Jurayj ابن جريج; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو (Sunan Abi Dawud)
A thief’s hand should be cut off for a quarter of a dinar and upwards. Ahmed b. Salih said: The amputation (of a thief’s hand) is for a quarter of a dinar and upwards.
Grade: Sahih

Hadith #4404 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I was among the captives of Banu Qurayzah. They (the Companions) examined us, and those who had begun to grow hair (pubes) were killed, and those who had not were not killed. I was among those who had not grown hair.
Grade: Sahih

Hadith #4512 - Sunan Abi Dawud - Abdur Rahman bin 'Abdullah bin Ka'b عبد الرحمن بن عبد الله بن كعب بن مالك; Abu Thaur al-Kalbi إبراهيم بن خالد أبو ثور الكلبي; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Umm Mubashir al-Ansariyya (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) would accept a present, but would not accept alms (sadaqah). And Wahb bin Baqiyyah narrated to us, elsewhere, from Khalid, from Muhammad ibn Amr said on the authority of AbuSalamah, and he did not mention the name of Abu Hurairah: The Messenger of Allah (ﷺ) used to accept presents but not alms (sadaqah). This version adds: So a Jewess presented him at Khaybar with a roasted sheep which she had poisoned. The Messenger of Allah (ﷺ) ate of it and the people also ate
Grade: Hasan Sahih

Hadith #4528 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Hasan al-Basri الحسن البصري; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qatada قتادة; Qays bin 'Aabad al-Qaysi قيس بن عباد القيسي الضبعي; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A Jew killed a girl of the Ansar for her ornaments. He then threw her in a well, and crushed her head with stones. He was then arrested and brought to the Prophet (ﷺ). He ordered regarding him that he should be stoned to death. He was then stoned till he died. Abu Dawud said: It has been transmitted by Ibn Juraij from Ayyub in a similar way.
Grade: Sahih

Hadith #4588 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Imran bin Husain; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Musaddad’s version has: He addressed on the day of Conquest. The agreed version then goes: Beware! Every object of pride of pre-Islamic times, whether it is blood-vengeance or property, mentioned or claimed, has been put under my feet except supply of water to the pilgrims and custody of the House (the Ka’bah). He then said: Beware! The blood-wit for unintentional murder, such as is done with a whip and stick, is one hundred camels, forty of which are pregnant.
Grade: Sahih

Hadith #4595 - Sunan Abi Dawud - Abdul Quddus bin al-Hajjaj al-Khulani عبد القدوس بن الحجاج الخولاني; Ahmad bin Hanbal أحمد بن حنبل; al-Azhar bin 'Abdullah al-Harazi أزهر بن عبد الله; Amr bin 'Uthman عمرو بن عثمان بن عفان; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Mu'awiya ibn Abu Sufyan; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي (Sunan Abi Dawud)
Al-Rubayyi’, sister of Anas b. al-Nadr, broke (one of) the front teeth of a woman. They came to the Prophet (ﷺ). He made a decision in accordance with the Book of Allah that retaliation should be taken. Anas b. al-Nadr said: I swear by Him who has sent you the truth, her front tooth will not be broken today. He replied: Anas ! Allah’s decree is retaliation. But the people were agreeable to accepting a fine, so the Prophet (ﷺ) said: Among Allah’s servants there are those who, if they ad
Grade: Sahih

Hadith #4601 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
I came to my family when my hands had cracks. They dyed me with saffron. I then went to Prophet (ﷺ) and saluted him, but he did not return me salutation. He said: Go and wash it away from you.
Grade: Hasan

Hadith #4603 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Abu Rafi'; Ahmad bin Hanbal أحمد بن حنبل; Salm Abi al-Nadr سالم بن أبي أمية - أبو النضر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Abi Dawud)
The Prophet (ﷺ) said: Controverting about the Qur’an is disbelief.
Grade: Hasan Sahih

Hadith #4605 - Sunan Abi Dawud - Abdur Rahman bin 'Amr bin 'Absa عبد الرحمن بن عمرو بن عبسة; Ahmad bin Hanbal أحمد بن حنبل; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Let me not find one of you reclining on his couch when he hears something regarding me which I have commanded or forbidden and saying: We do not know. What we found in Allah’s Book we have followed.
Grade: Sahih

Hadith #4611 - Sunan Abi Dawud - Abdullah bin Yazid bin Zayd; Ahmad bin Hanbal أحمد بن حنبل; Nafie' نافع مولى ابن عمر; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي (Sunan Abi Dawud)
Whenever he (mu’adh b. jabal) sat in a meeting for preaching, he would say: Allah is a just arbiter; those who doubt would perish. One day Mu’adh b. jabal said: In the times after you there would be trails in which riches would be abundant. During these trails the Quran would be easy so much so that every believer, hypocrite, man, woman, young, grown up, slave and free man will learn it. Then a man might say: What happened with the people that they do not follow me while I read the Quran? Th
Grade: Sahih

Hadith #4675 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Abbas; Nasr bin 'Imran bin Isam نصر بن عمران بن عصام; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say : I am the nearest of kin among the people to (Jesus) son of Mary. The Prophet are brothers, sons of one father by co-wives. There is no Prophet between me and him.
Grade: Sahih

Hadith #4676 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Faith has over seventy branches, the most excellent of which is the declaration that there is no god but Allah, and the humblest of which is the removal of a bone from the road. And modesty is a branch of faith.
Grade: Sahih

Hadith #4680 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
when the Prophet (May peace be upon him) turned towards the Ka’bah (in prayer), the people asked : Messenger of Allah (May peace be upon him)! what will happen with those who died while they prayed with their faces towards Jerusalem ? Allah the Exalted, then revealed : “And never would Allah make your faith of no effect.”
Grade: Sahih

Hadith #4683 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Ma'mar bin Rashid معمر بن راشد; Sa'd ibn Abi Waqqas (Sunan Abi Dawud)
The Prophet (May peace be upon him) gave some people and did not give anything to a man of them. Sa’d said : Messenger of Allah! You gave so and so, so and so, but did not give anything to so and so while he is a believer. The Prophet (May peace be upon him) said : Or he is a Muslim. Sa’d repeated it thrice and the Prophet (May peace be upon him) then said : I give some people and leave him who is dearer to me than them. I do not give him anything fearing lest he should fall into Hell on his
Grade: Sahih

Hadith #4708 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Ata'a bin Dinar al-Hdhly عطاء بن دينار الهذلي مولاهم; Hakeem bin Sharik al-Hadhli حكيم بن شريك الهذلي; Rabi'yah al-Jrshy ربيعة الجرشي; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي; Umar ibn al-Khattab; Yahya bin Maymun al-Hdrmy يحيى بن ميمون الحضرمي (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) who spoke the truth and whose word was belief told us the following : The constituents of one of you are collected for forty days in his mother’s womb, then they become a piece of congealed blood for a similar period, then they become a lump of flesh for a similar period. Then Allah sends to him an angel with four words who records his provision the period of his life, his deeds, and whether he will be miserable or blessed ; thereafter he breathe
Grade: Sahih

Hadith #4780 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Abu Harb bin Abi al-Aswad أبو حرب بن أبي الأسود الديلي; Ahmad bin Hanbal أحمد بن حنبل; Da'ud bin Abi Hnd داود بن أبي هند; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير (Sunan Abi Dawud)
Two men reviled each other in the presence of the Prophet (ﷺ) and one of them became excessively angry so much so that I thought that his nose will break up on account of excess of anger. The Prophet (ﷺ) said: I know a phrase which, if he repeated, he could get rid of this angry feeling. They asked: What is it, Messenger of Allah? He replied: He should say: I seek refuge in Thee from the accursed devil. Mu’adh then began to ask him to do so, but he refused and persisted in quarrelling, and
Grade: Da'if

Hadith #4950 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: Call yourselves by the names of the Prophets. The names dearest to Allah are Abdullah and AbdurRahman, the truest are Harith and Hammam, and the worst are Harb and Murrah.
Grade: Sahih

Hadith #4957 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Samra bin Jundub; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan Abi Dawud)
Masruq said: I met Umar ibn al-Khattab (Allah be pleased with him) who said: Who are you? I replied: Masruq ibn al-Ajda’. Umar then said: I heard the Messenger of Allah (ﷺ) say: al-Ajda’ (mutilated) is a devil.
Grade: Da'if

Hadith #4959 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Ahmad bin Hanbal أحمد بن حنبل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The Aposlte of Allah (May peace be upon him) forbade giving four names to our slaves : Aflah (successful), Yasar (wealth), Naf(beneficial) and Rabah (profit).
Grade: Sahih

Hadith #5018 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
A believer’s vision is the forty-sixth part of Prophecy.
Grade: Sahih

Hadith #5132 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-'Ala' bin al-Hadrami; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ibn Sirin محمد بن سيرين الأنصاري; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي (Sunan Abi Dawud)
Make intercession, you will be rewarded, for I purposely delay a matter so that you intercede and then you are rewarded. The Messenger of Allah (ﷺ) said: If you make intercession, you will be rewarded.
Grade: Sahih

Hadith #5196 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
(This version is same as previous No 5176 from the Prophet (ﷺ), adding that): Afterwards another man came and said: Peace and Allah’s mercy, blessings and forgiveness be upon you! whereupon he said: Forty. adding: Thus are excellent qualities rewarded.
Grade: Da'if

Hadith #5206 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of the Jews greets you saying: Death may come upon you, reply: The same to you. Abu Dawud said: Malik b. ‘Adb Allah b. Dinar transmitted it in a similar manner, and al-Thawri transmitted it from ‘Abd Allah b. Dinar. He said in this version: The same to you.
Grade: Sahih

Hadith #5244 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Abu Dharr through a different chain of narrators. In this version the transmitter mentioned the Prophet(ﷺ) in the middle of the tradition.
Grade: Sahih

Hadith #5260 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Ma'mar bin Rashid معمر بن راشد; Sa'd ibn Abi Waqqas (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was asked about the house-snakes. He said: When you see one of them in your dwelling, say: I adjure you by the covenant which Noah made with you, and I adjure you by the covenant which Solomon made with you not to harm us. Then if they come back, kill them.
Grade: Da'if

Hadith #5265 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
A prophet got down beneath a tree and he was stung by an ant. He ordered regarding the baggage and it was removed from beneath it. He then ordered regarding it and it was burnt. Allah then revealed to him : why not (just) one ant?
Grade: Sahih